PELATIHAN PENYUSUNAN ANGGARAN BERBASIS KINERJA DI SMP MUHAMMADIYAH 6 DAU - Juanda, Ahmad; Setyawan, Setu; Oktavendi, Tri Wahyu (Universitas Muhammadiyah Malang, 2021)
This service focuses on Performance-Based Budgeting at Muhammadiyah 06 Dau School, Malang Regency. The purpose of this service is to improve the quality, realization, and evaluation of performance appraisals. The method used in the community service program uses a method that goes through stages, namely: Determining the vision, mission and goals; Determination of Activities; FGD for preparation of budget components. The results of this training are in the form of knowledge and expertise in performance budgeting. The pre-test score of the training participants was on average 60 and after the training was carried out the average score increased to 93.Based on the preparation of the performance-based School Budget Work Plan (RKAS) it can be denied that the participants in the performance-based preparation of the School Budget Work Plan (RKAS) are 5 people consisting of the school principal and school treasurer. The results of this dedication show that the trainees should not only be school principals and treasurers, but teachers and teaching aids should not be alone but need to be supplemented with adequate computer facilities. The implication of this service is financial performance of Muhammadiyah 06 Dau School more effective and Efficient.